MLL-AF9 and MLL-ENL alter the dynamic association of transcriptional regulators with genes critical for leukemia - Monroe, Sara C.; Jo, Stephanie Y.; Sanders, Daniel S.; Basrur, Venkatesha; Elenitoba-Johnson, Kojo S.; Slany, Robert; Hess, Jay L. (Experimental Hematology, 2011)
Objective: The aim of this study was to better understand how mixed lineage leukemia (MLL) fusion proteins deregulate the expression of genes critical for leukemia. Materials and Methods: The transforming domain of one of the most common MLL fusion partners, AF9, was immunopurified after expression in myeloblastic M1 cells, and associating proteins were identified by mass spectrometric analysis. Chromatin immunoprecipitation followed by quantitative polymerase chain reaction was used to determine how binding of associating proteins compare across Hoxa9 and Meis1 in cell lines with and without MLL fusion proteins and how binding is altered during gene down-regulation and differentiation. Results: Consistent with earlier purifications of ENL and AF4 from 293 cells, the 90 amino acid C-terminal domain of AF9 associates with many other MLL translocation partners including Enl, Af4, Laf4, Af5q31, Ell, and Af10. This complex, termed elongation assisting proteins (EAPs), also contains the RNA polymerase II C-terminal domain kinase Cdk9/Cyclin T1/T2 (pTEFb) and the histone H3 lysine 79 methyltransferase Dot1L. Myeloid cells transformed by MLL fusions show higher levels and a broader distribution of EAP components at genes critical for leukemia. Inhibition of EAP components pTEFb and Dot1l show that both contribute significantly to activation of Hoxa9 and Meis1 expression. EAP is dynamically associated with the Hoxa9 and Meis1 loci in hematopoietic cells and rapidly dissociates during induction of differentiation. In the presence of MLL fusion proteins, its dissociation is prevented. Conclusions: The findings suggest that MLL fusion proteins deregulate genes critical for leukemia by excessive recruitment and impaired dissociation of EAP from target loci. © 2011 ISEH - Society for Hematology and Stem Cells.